Serum bile acid levels as a predictor for the severity of liver fibrosis in patients with chronic hepatitis C. Issue 2 (3rd August 2012) - Shlomai, A.; Halfon, P.; Goldiner, I.; Zelber‐Sagi, S.; Halpern, Z.; Oren, R.; Bruck, R.
<x xml:space="preserve">Abstract</x> Summary. Serum bile acids (SBAs) are commonly elevated in cholestatic liver diseases, but it is unclear if SBA levels are also elevated in noncholestatic chronic liver diseases and whether those levels correlate with disease severity. We analysed SBA levels of 135 consecutive patients with chronic hepatitis C virus infection and correlated these levels with the degree of liver fibrosis as determined by liver biopsy. In addition, we assessed the accuracy of SBA levels as a noninvasive predictor for liver fibrosis by its comparison to the patients' FibroTest scores. Two‐thirds (90/135 patients, 67%) of the study patients had nonsevere liver fibrosis (Metavir F0–F2), and the others (45/135, 33%) had severe fibrosis or cirrhosis (Metavir F3–F4). The SBA levels were significantly higher in patients with severe fibrosis as compared to nonsevere fibrosis (11.46 ± 10.01 vs 6.37 ± 4.69, P < 0.0001). Furthermore, a receiver operator characteristics curve based on a model that included serum bile acids, age, body mass index, serum AST, glucose and cholesterol levels suggested that this combination reliably predicts the degree of liver fibrosis and is not inferior to the current noninvasive FibroTest score (areas under the curve of 0.837 vs 0.83, respectively, P = 0.87). We conclude that measurement of SBA levels may have a clinical role as a simple noninvasive tool to assess the severity of HCV‐induced liver disease. Combined with widely available laboratory parameters, SBA levels can predict disease severity with a high degree of accuracy.